Business study seminar (Europe) the institutional make-up of the European Union. - Eu, Jo-Anne Chu Chuin. (2011)
The European Coal and Steel Community was conceived as an economic union by the Treaty of Paris (1951) to end intra-European conflict. It was refined by the Treaty of Rome (1957), the Maastricht Treaty (1992) and the Treaty of Amsterdam (1998) to encompass social, legal, political and defence integration and especially monetary union, resulting in the European Union (EU). The EU comprises 15 constitutional members with 11 more applying for membership. The EU is administered by 10 institutions, covering the full range of governmental duties. The Council of Ministers, with the heads of each country as its representative, and the European Parliament with 626 representatives from throughout the EU, are the main legislative arms of the Union. The European Commission, through its 26 Directorates General(DGs), is the main executive body, while the Court of Justice is the judiciary. The other institutions support the functioning of the EU, ensuring that there is a just and equitable application of the union's powers and authority by the proper persons in an accountable manner.